New Zealand Diastylidae and Gynodiastylidae (Crustacea: Cumacea) - Gerken, Sarah (Zootaxa, 2015)
Recent work in the collections at the New Zealand National Institute of Water and Atmospheric Research collections in Wellington has yielded 14 new diastylid species in five genera, Colurostylis whitireia n. sp., Diastylis acanthoelachys n. sp., D. adaioacanthus n. sp., D. curtain n. sp., D. dasys n. sp., D. enodis n. sp., D. homoacanthus n. sp., D. implanus n. sp., D. spinacellulosus n. sp., Diastylopsis aspratilis n. sp., D. bicarina n. sp., Leptostylis wisniewskiae n. sp., L. zealandiensis n. sp., Makrokylindrus semiechinata n. sp. and a single new gynodiastylid species, Gynodiastylis chathamensis n. sp. Makrokylindrus is recorded from New Zealand waters for the first time. Keys to all diastylid and gynodiastylid species from New Zealand waters are included, as well as an updated global key to Diastylopsis.